Morphology and optical properties of nickel oxide nanostructure from aqueous solution - Hamid M.A.A.; Bakar M.A.; Jalar A.; Shamsudin R.; Ahmad I. (2023)
In this paper, porous flower-like nickel oxide (NiO) on glass substrates were prepared by an aqueous chemical growth based technique. The morphology and optical observed were found to be influence by the reaction time. Field Emission Scanning Electron Microscopy (FESEM) revealed a porous flower-like structure growth on the substrates investigated. The optical band gap for NiO thin film calculated from transmission spectra has increased from 3.72 eV to 3.91 eV with the increasing of reaction time. This result shows that the growth time have some influence on morphology and optical of NiO films.